F & B portal (tracking system and messaging notification) / Farah Azila Fazen - Fazen, Farah Azila (2013)
Burger King a global chain of hamburger fast food restaurants. There are currently, three franchise holders in Malaysia. Nowadays the computer technology becomes very important in daily life. One of the problems in technology is data storage and management. Before F & B Portal be implemented, users itself have to face many steps to make an order in Burger King. Besides, admin staffs are facing problem with the manual system to record the data. The main objective is to clearly tracking system and messaging notification for F & B Portal. Thus, users are able to check the location of the ordered item in online ordering sub portal. With this F & B Portal system, users can simply make order and view it through website to keep track the status of their order. Therefore, F & B Portal system is proposed. The strength of F & B system is that it centralized Online Food Ordering system in one web system which is include tracking and messaging system to make user more easier to track their order. This system is useful for admin and staffs for them to update any incoming orders in which stage of production.